The Effect of Training Methods and Concentration on The Result of Free Shooting on Extracurricular Woman’s Basketball in SMA Negeri Mayong - Nur, Muh Daviq; Sulaiman, Sulaiman; Irawan, Fajar Awang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to determine the difference effect between training methods using ropes and hoops on free-throw results with different concentration levels, differences in free throw shooting skills between students who have high and low concentration levels, the effect of interaction between training methods and concentration levels on shooting ability free throw. This study uses an experimental method with a 2 x 2 factorial design. The data analysis technique in this study uses ANOVA. Based on the results of the study, there was a significant difference in effect between the training methods using rope and hoops to the results of free-throw shooting (Fvalue = 4.87 and Ftable = 4.26), there were significant differences in the results of free-throw shooting abilities between students who had high levels of concentration and low (Fvalue = 4.31 and Ftable = 4.26), there is a significant interaction effect between the training method and concentration level on the results of free-throw shooting (Fvalue = 5.74 and Ftable = 4.26). The conclusion from the results of the study is the training method, and the concentration level is the variables that influence the increased ability to do free throws. Each player has different abilities, especially when someone is under pressure, which certainly cannot provide maximum results. Every trainer must understand this condition by giving some specific training and treatment methods as a solution.